RESOURCES OF SCALP FISH (Trichiurus lepturus) AND ITS FISHING GEAR IN CILACAP WATERS - Ernaningsih, Dwi; Bintoro, Sigit; Rahmani, Urip (Lembaga Penelitian, Publikasi, & Pengabdian kepada Masyarakat, Universitas Satya Negara Indonesia (LP3M-USNI), 2024)
Hairtail is one commodities of fish economically important that be caught in Cilacap waters. The increased demand of hairtail in every years, caused hairtail resources potentially exploited as great as possible and when not controlled will caused disturbed hairtail resources. This study aims were to analysis fisheries biology condition of hairtail in Cilacap waters and to analyse fishing gear effectiveness. Research implemented in November to Desember 2014 on fish landing sites (TPI) Pandanarang, Tegal Katilayu, Lengkong and surrounding Cilacap waters. The research methodology was a survey method to fish catching activities with sirang nets (drift gillnet), payang nets (denish seine) and arad nets. Fisheries biology conditions analyzed with fishing gear effectiveness analyzed with catch per unit effort (CPUE) every fishing gear. The result of research were range in total length and length mode 25,2- 79,9 cm and 69 cm, range in weight and weight mode 15- 285 gram and 165 gram. Growth pattern of hairtail was negative allometric. Efective fishing gear was drift gillnet with CPUE was 0,57 ton/units.